A survey of the awareness, knowledge, policies and views of veterinary journal Editors-in-Chief on reporting guidelines for publication of research - Grindlay, Douglas J.C.; Dean, Rachel S.; Christopher, Mary M.; Brennan, Marnie L. (BioMed Central, 2014)
Background: Wider adoption of reporting guidelines by veterinary journals could improve the quality of published veterinary research. The aims of this study were to assess the knowledge and views of veterinary Editors-in-Chief on reporting guidelines, identify the policies of their journals, and determine their information needs. Editors-in-Chief of 185 journals on the contact list for the International Association of Veterinary Editors (IAVE) were surveyed in April 2012 using an online questionnaire which contained both closed and open questions. Results: The response rate was 36.8% (68/185). Thirty-six of 68 editors (52.9%) stated they knew what a reporting guideline was before receiving the questionnaire. Editors said they had found out about reporting guidelines primarily through articles in other journals, via the Internet and through their own journal. Twenty of 57 respondents (35.1%) said their journal referred to reporting guidelines in its instructions to authors. CONSORT, REFLECT, and ARRIVE were the most frequently cited. Forty-four of 68 respondents (68.2%) believed that reporting guidelines should be adopted by all refereed veterinary journals. Qualitative analysis of the open questions revealed that lack of knowledge, fear, resistance to change, and difficulty in implementation were perceived as barriers to the adoption of reporting guidelines by journals. Editors suggested that reporting guidelines be promoted through communication and education of the veterinary community, with roles for the IAVE and universities. Many respondents believed a consensus policy on guideline implementation was needed for veterinary journals. Conclusions: Further communication and education about reporting guidelines for editors, authors and reviewers has the potential to increase their adoption by veterinary journals in the future.